A Comparison of Selected Aspects of Finnish and Polish Public Libraries - Antczak, Mariola (Folia Scandinavica Posnaniensia, 2014)
The article presents and compares the general situation of public libraries and readership in Finland and Poland at the beginning of the 21st century, based on selected statistical data on the topic. In order to correctly understand the library policy of Finland - a country in which it is impossible to implement cultural policy without taking into account the geographical and natural conditions of individual regions - the most important data on the country are presented and compared with data on Poland. Statistical schedules, online reports on the activity of public libraries, libraries’ homepages, legislative acts and professional library science magazines, among others, served as source materials for the conducted analysis. The comparative method, documentation analysis method and statistical method were used to achieve the assumed objectives. Considering the limitations on the article size, a decision was made to select a few specific aspects of the topic for analysis - the most important ones in the author’s opinion. Among others, these included information on public libraries made available in both countries, contemporary government policies implemented towards the institutions that the author is interested in, conducting qualitative and quantitative research, generating reports on the research, as well as the governments’ compliance with international and national standards of the quality of library collections, personnel and services.